Folklore Archives of Pskov State University: From field recordings to remote access - Lishenko, Nadezhda (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
Here is a brief analysis of the folk fund of Pskov State University. The purpose is study the process of obtaining the folklore collections in an electronic form, accessible to remote users. The article contains the location of folklore materials – scientific and educational regional laboratory of philological research. It describes the objects and the structure of the funds and passport data of materials, examples of passport data of materials, describes the content of the collections. Expedition activity of the University began in 1977. Technical means of recording changed from tape recorder to electronic recorder. Nowadays the collection has more than 1,000 audio tapes. Most of them are digitized. Handwritten fund folklore archive in Pskov State University consists of student transcripts and audio commentaries on them. There are indications of some of the genre features of the archive. There is mentioning on wedding folklore, folk-listed holidays in church calendar. The names of festivals and songs remain largely a local name, with the exception of the Easter ritual songs in the yards, known among folklorists as valachobny. The article refers to over 30 types of folk songs that are stored in the archives of the Pskov State University, lists the genre of children's folklore, points the features of fairy-tales of the Pskov region in line with the types of ciphers fabulous on "Comparative index of subjects: The Eastern Tale" (L., 1979), and also discloses the concept of "supporting material". In the archive there are developed principles of scientific systematization and classification of folk materials. The principles of scientific and folk materials classification were developed. Systematic work for the storage of folklore materials is conducted up to date with the use of information techniques. Three thematic electronic data-base were established. The first is devoted to tales of the Pskov region. The second one gathers collection of verbal stories about the Great Patriotic War. The third database is dedicated to children's folklore. The article describes the structure of the databases and opportunities for research, compares search capabilities at the index (G. Ploschuk, 2003). Folklore Pskov region: Index of materials folklore archive PSPI. Part 1 and Part 2. Pskov: PSPI named after Kirov), and with the help of an electronic database. The access to the database is local. However, in the scientific and educational laboratory of the regional philological research in Pskov State University much work is done actively developing the resource of remote access. The author comes to the conclusion that the stages which folk songs are going through before they become an object of study for the researcher, are links in one chain.